Frailty and use of treatment in patients with heart failure and reduced ejection fraction. (3rd October 2022) - Kondo, T; Adachi, T; Kobayashi, K; Okumura, T; Izawa, H; Murohara, T; McMurray, J J V; Yamada, S
Abstract: Background: In heart failure with reduced ejection fraction (HFrEF), drugs including angiotensin-converting enzyme inhibitors (ACEi)/ angiotensin receptor blockers (ARB), beta-blockers, and mineralocorticoid receptor antagonists (MRA) have been shown to have robust survival benefits. However, these guideline-recommended therapies remain underutilized in clinical practice. Frailty is common in HFrEF and may lead to underprescription of life-saving therapy. Purpose: We aimed to investigate the association between physical frailty and the use of evidence-based pharmacological therapy for HFrEF, and the impact of this on prognosis Methods: The FLAGSHIP study included patients hospitalized for acute HF and data on physical frailty were collected prospectively. Of the total 3, 272 patients registered in the FLAGSHIP study, 1, 041 HFrEF patients (70 years; 73% male) with left ventricular ejection fraction ≤40% were analyzed and were divided into 4 groups by severity of frailty: category I (n=371) [least frail], II (n=275), III (n=224), and IV (n=171) [most frail]. Results: An ACEi/ARB was prescribed in 76% of category I and 53% of category IV patients; for a beta-blocker these proportions were 94% and 76%, respectively; for an MRA they were 55% and 46%, respectively. The proportion of patients using receiving all 3 drugs decreased as frailty increased, with approximately twice the rate of use of triple therapy in category I patients (40.2%) compared to category IV patients (23.4%) [p<0.001] (Figure 1). In adjusted analyses, the severity of frailty was an independent predictor for non-use of an ACEi/ARB (Odds ratio (OR): 1.23, 95% CI: 1.05–1.43, per 1 category increase) and a beta-blocker (OR: 1.32, 95% CI: 1.06–1.64), but not an MRA (OR: 0.97, 95% CI: 0.84–1.12). Risk of the composite outcome of all-cause death or HF rehospitalization increased with decreasing use of treatment across frailty categories: category I-II (Hazard ratio (HR): 1.80, 95% CI: 1.08–2.98, in 0–1 drug with 3 drugs as reference) and III–IV (HR: 1.53, 95% CI: 1.01–2.32). The relationship between the number of HF drugs prescribed and the composite outcome did not differ across frailty categories (p-interaction=0.86). The HRs for all 12 groups, reflecting frailty categories and a number of HF drugs is depicted in Figure 2. The HRs for composite outcome increased with increasing frailty category and with decreasing number of drugs, with an almost 4-fold difference in risk between the least frail patients receiving all three evidence-based therapies and the most frail receiving only 0–1 drug. Conclusions: Prescription of guideline-recommended therapy decreased as the severity of frailty increased in patients with HFrEF. Sub-optimal medical therapy was associated with a worse outcome and underprescription of guideline-recommended therapy may contribute to the poor prognosis associated with frailty. An effective strategy is needed to improve the medical treatment of frail patients with HFrEF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This study issupported by a Grant-in-Aid for Scientifi c Research (A) from the Japan Society for the Promotion of Science (16H01862). ToruKondo receives grants from the Uehara Memorial Foundation and the Japanese Heart Failure Society Tsuchiya Foundation forthe research activities at the University of Glasgow.